ANALISIS HUKUM PEMUTUSAN HUBUNGAN KERJA PADA MASA PANDEMI COVID -19 - I Komang Edy Dharma Saputra (Jurnal Ilmiah Raad Kertha, 2021)
The protection of workers and workers gets special attention in the concept of the rule of law relating to human rights. The issue of termination of employment has received an additional burden since the entry of the Covid-19 pandemic. Protection for workers and workers in the current pandemic situation can be linked to the concept of the rule of law related to the context of Human Rights. The COVID-19 pandemic has had a negative impact on the national economy. This of course can trigger companies to terminate their employment, because some companies are no longer able to pay the salaries of their workers. The termination of employment is considered to be a path that must be used by employers to avoid significant losses. This will certainly have an impact on increasing the number of unemployed in Indonesia.